Effect of preceding home‐visit nursing on time to discharge in hospitalization for the treatment of behavioural and psychological symptoms of dementia among patients with limited familial care. Issue 1 (26th January 2018) - Kitamura, Tatsuru; Shiota, Shigehito; Jinkawa, Shigetoshi; Kitamura, Maki; Hino, Shoryoku
Abstract : Background: During hospitalization for behavioural and psychological symptoms of dementia (BPSD), it is imperative to build a support system for each patient in the community for after they obtain symptom remission. To this end, patients lacking adequate family support are less likely to be discharged to their own homes and need stronger support systems to be established. This study therefore investigated the effects of home‐visit nursing before admission on time to home discharge among patients with limited familial care who were hospitalized for treatment of BPSD. Methods: A single‐centre chart review study was conducted on consecutive patients admitted from home between April 2013 and September 2015 for treatment of BPSD and who had lived alone or with a working family member. Time to home discharge was compared between patients who had home‐visit nursing before their admission and those who did not. Results: In total, 58 patients were enrolled in the study, of whom 12 had preceding home‐visit nursing (PHN group) and 46 did not (non‐PHN group). Patients in the PHN group were younger (77.7 ± 4.9 vs. 84.1 ± 6.1 years, P = 0.0011) and had higher Mini‐Mental State Examination scores (16.8 ± 7.2 vs 11.8 ± 7.3, P = 0.0287). A multivariate Cox proportional hazard regression analysis adjusted for age and Mini‐Mental State Examination scores showed a higher likelihood of discharge to home in the PHN group (hazard ratio: 3.85; 95% confidence interval: 1.27–11.6;, P = 0.017) than in the non‐PHN group. Conclusion: Home‐visit nursing before admission of BPSD patients for treatment could improve the rate of discharge to home among patients with limited familial care after subsequent hospitalization. Home‐visit nursing could also enhance collaborative relationships between social and hospital‐based care systems, and early implementation could improve the likelihood of vulnerable patient types remaining in their own homes for as long as possible.